TEN telecom guidelines status review - Cave, Jonathan A. K., 1951-; Botterman, Maarten; Ellens, Renske; Luoma, Paivi; de Vries, G. J. (Gert Jan); Westerhof, Roel.; Rand eBooks (Santa Monica, CA : RAND, 2003)
The 1992 Maastricht Treaty of the European Community calls for the creation of Trans-European Networks, or TENs, in transport, telecommunications, and energy. The TENs, supported with a budget of 4.6 billion Euro for 2000-2006, support projects of common interest where immediate commercial prospects and benefits are uncertain but that promote interconnection and interoperability of and universal access to national transport, telecommunications, and energy networks. Article 14 of the TEN Telecom Guidelines requires the Commission in 2001 to revise Annex 1 of the Guidelines, which provides specific guidance to projects, to reflect technical developments and lessons of experience learned to date. To assess the future needs and prospects for the TEN Telecom Action and to develop a vision by which to revise its guidelines, RAND Europe and IDC Benelux conducted a technology foresight study examining emergent technological solutions and needs, a survey among sector users, and in-depth interviews with sector members. This document presents a medium-term vision and has been important input to the European Commission in preparation of its proposals for a revision, which has now been agreed with the European Parliament and the EU Member States.
Executive Summary -- Introduction -- Findings -- Recommendations -- Appendix 1: Main Findings of the Foresight Study -- Appendix 2: Powerpoint Presentation of Main Findings.
"RAND Europe / IDC Benelux."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Energy policy -- European Union countries; Information policy -- European Union countries; Information technology -- Economic aspects -- European Union countries; Information technology -- Government policy -- European Union countries; Infrastructure (Economics) -- European Union countries; Technological innovations -- Economic aspects -- European Union countries; Telecommunication policy -- Europe; Transportation and state -- European Union countries; Transportation -- European Union countries; Electronic books